Autonomous sensory meridian response (ASMR) and frisson: Mindfully induced sensory phenomena that promote happiness. Issue 2 (2nd April 2016) - del Campo, Marisa A.; Kehle, Thomas J.
Abstract : There are many important phenomena involved in human functioning that are unnoticed, misunderstood, not applied, or do not pique the interest of the scientific community. Among these, autonomous sensory meridian response (ASMR) and frisson are two very noteworthy instances that may prove to be therapeutically helpful in promoting subjective well-being or happiness, which can be considered synonymous with mental health. This review attempts to elucidate the characteristics of each phenomenon, including proposed similarities and differences between the two. We present an argument that ASMR and frisson are interrelated in that they appear to arise through similar physiological mechanisms, and both may be induced or enhanced through the practice of mindfulness.